IFN-CSP Inhibiting Hepatitis B Virus in HepG2.2.15 Cells Involves JAK-STAT Signal Pathway. (16th March 2015) - Lu, Xuemei; Wang, Jie; Jin, Xiaobao; Huang, Yanting; Zeng, Wenting; Zhu, Jiayong
Abstract : Frequent and high-dose administration of interferon to patients with viral hepatitis results in various side effects. In our previous study, a novel liver-targeting interferon (IFN-CSP) combining Plasmodium region I peptide with IFN α 2b was successfully designed and expressed in the Escherichia coli expression systems. This targeting would target the IFN α 2b specifically to the liver, thus reducing the adverse events. In the present study, we further investigated the anti-HBV effects and molecular mechanisms of recombinant IFN-CSP in HepG2.2.15 cell line. Hepatitis B surface antigen (HBsAg) and HBe antigen (HBeAg) in the culture supernatants were analyzed by enzyme-linked immunosorbent assay (ELISA). HBV-DNA was measured by real-time quantitative PCR. HBV core protein was assayed by immunofluorescent and western blot analysis. The expressions of signal transducers and transactivator 1 (STAT1), STAT2, IFN regulatory factor 9 (IRF-9), and 2′-5′-oligoadenylate synthetase 1 (OAS1) were investigated by the reverse transcription PCR and western blot analysis. Results indicate IFN-CSP efficiently inhibited HBsAg and HBeAg secretion, HBV-DNA replication, and HBV core protein expression in HepG2.2.15 cells. The anti-HBV mechanisms involve activation of JAK-STAT signaling and increase of the anti-HBV protein OAS expression. IFN-CSP could be a good substitute for IFN α 2b for anti-HBV treatment.